The Social Affordances of the Internet for Networked Individualism - Wellman, Barry; Quan‐Haase, Anabel; Boase, Jeffrey; Chen, Wenhong; Hampton, Keith; Díaz, Isabel; Miyata, Kakuko (Journal of computer-mediated communication, 2003)
We review the evidence from a number of surveys in which our NetLab has been involved about the extent to which the Internet is transforming or enhancing community. The studies show that the Internet is used for connectivity locally as well as globally, although the nature of its use varies in different countries. Internet use is adding on to other forms of communication, rather than replacing them. Internet use is reinforcing the pre‐existing turn to societies in the developed world that are organized around networked individualism rather than group or local solidarities. The result has important implications for civic involvement.